Adverse Childhood Experiences: A Case-Based Workshop Introducing Medical Students to Trauma-Informed Care - Beth A. Pletcher; Mary O'Connor; Mary Elizabeth Swift-Taylor; Michelle DallaPiazza (Association of American Medical Colleges, 2019)
Introduction A large body of evidence implicates adverse childhood experiences (ACEs) as significant factors in shaping adult health outcomes. Despite their wide-ranging impact on health, training on ACEs is lacking in most medical school curricula. As part of a required health equity course for first-year medical students, we developed a novel workshop on ACEs with an introduction to protective effects of resilience and trauma-informed care. Methods This educational module on ACEs incorporated a didactic session on the science and health consequences of ACEs and best practices for trauma-informed care, followed by a facilitated case discussion in small groups exploring an ACE survey tool and a resilience questionnaire. Results A total of 535 first-year medical students participated in the workshop in academic years 2016-2017, 2017-2018, and 2018-2019. In the session evaluation, students reported that the small-group, case-based discussion provided the richest learning experience. Areas identified by the students for improvement included delving more deeply into how to incorporate asking about ACEs in clinical care and how to involve multidisciplinary services in addressing ACEs. Discussion The focus on raising awareness of the health impact of ACEs as well as enhancing resilience using a case-based approach was successful in meeting the stated objectives for the workshop. Future work will consist of building on this introductory content by designing curricular elements that explore multidisciplinary approaches to ACEs and trauma-informed care interventions in the clinical clerkships.